Prince - Machiavelli, Niccolo (Oxford, 1979)
The Prince is the Bible of realpolitik. This famous treatise on statecraft holds such power to shock 'men of goodwill' that at one time Niccolò Machiavelli (1469-1527) was identified with Satan himself. In his own turbulent times, however, Machiavelli was concerned, not with lofty ideals, but with government that would last. He drew on his own experience of office under the Florentine Republic. Here he states uncompromisingly what, in some degree, most governments do but none profess to do, and the tough realities of Machiavelli's Italian are well preserved in the clear, unambiguous English of George Bull's translation.
Keywords: Political science